Prognostic Analysis for Patients With Parathyroid Carcinoma: A Population-Based Study - Qian, Bei; Qian, Ying; Hu, Longqing; Zhang, Shoupeng; Mei, Li; Qu, Xincai (Frontiers in Neuroscience, 2022)
Background: Parathyroid carcinoma (PC) is a rare, but often lethal malignancy, for which staging system, prognostic indicators and treatment guidelines is still not established. We aimed to explore the prognostic parameters and construct a nomogram for cancer-specific survival (CSS) of PC. Methods: A retrospective analysis of 604 PC patients in the SEER database from 2001 through 2018 was performed. All the cases were randomly assigned to the training cohort (n=424) or the validation cohort (n =180) at a ratio of 7:3. Kaplan-Meier method and cox regression model was applied to estimate the CSS and risk factors, and a nomogram was constructed. The predictive accuracy and discriminative ability of the nomogram in CSS were assessed by concordance index (C-index), the area under the curve (AUC) of operating characteristics (ROC) and calibration curve. Results: Age at diagnosis > 70 years (hazard ratio (HR): 3.55, 95% confidence interval (CI):1.07-11.78, P = 0.039), tumor size > 35mm (HR:4.22; 95%CI:1.67-10.68, P = 0.002) were associated with worse CSS. Compared with distant metastasis, localized (HR:0.17; 95%CI:0.06-0.47, P = 0.001) and regional lesions (HR:0.22; 95%CI:0.07-0.66, P = 0.007) showed an improved CSS rate. Parathyroidectomy was the recommended treatment (P = 0.02). The C-index of the nomogram was 0.826, and AUC for 5-, 10-, and 15-year-CSS was 83.7%, 79.7% and 80.7% respectively. The calibration curve presented good agreement between prediction by nomogram and actual observation. Conclusion: Age at diagnosis >70 years, tumor size >35mm, and distant metastasis were independent risk factors for PC-specific mortality. Parathyroidectomy were currently the most recommended treatments for PC. This nomogram provided individualized assessment and reliable prognostic prediction for patients with PC.